2020
DOI: 10.1093/biolinnean/blaa002
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the dots: avian eggshell pigmentation, female condition and paternal provisioning effort

Abstract: Differences in avian eggshell pigmentation could be an honest signal of female quality that males use to inform their nestling provisioning effort. We investigated whether among-individual variation in protoporphyrin-based eggshell pigmentation in house wrens (Troglodytes aedon) reflects female fitness-associated traits and whether males use that information. Females laying lighter clutches were older and larger than females laying darker clutches. Nestlings hatching from lighter clutches had greater size-corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Eggshell pigmentation is an extended phenotypic trait of female birds, one that may provide information about a female's underlying physiological condition (Moreno and Osorno 2003;Moreno et al 2006;Hodges et al 2020) as well as serve as an adaptation for camouflaging eggs (Poulton 1890: 61ff. ;Lack 1958;Weidinger 2001;Westmoreland and Kilti 2007), strengthening eggshells (Underwood and Sealy 2002;Gosler et al 2005), and, for the embryo, mediating light exposure and modulating the thermal environment (Bakken et al 1978;Mauer et al 2015;Lahti and Ardia 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eggshell pigmentation is an extended phenotypic trait of female birds, one that may provide information about a female's underlying physiological condition (Moreno and Osorno 2003;Moreno et al 2006;Hodges et al 2020) as well as serve as an adaptation for camouflaging eggs (Poulton 1890: 61ff. ;Lack 1958;Weidinger 2001;Westmoreland and Kilti 2007), strengthening eggshells (Underwood and Sealy 2002;Gosler et al 2005), and, for the embryo, mediating light exposure and modulating the thermal environment (Bakken et al 1978;Mauer et al 2015;Lahti and Ardia 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In house wrens (Troglodytes aedon Vieillot, 1809), the ground (base) color of the eggshell varies from white to light tan or pink, and it is either sparsely or densely maculated with D r a f t 4 small spots or larger blotches of reddish brown (Johnson 2020;Hodges et al 2020). In a recent study relating protoporphyrin-based eggshell pigmentation to female condition and levels of male parental provisioning in our study population, we found that females laying eggs with more sparsely maculated and redder shells were older and produced heavier offspring than females laying more densely maculated and browner eggs (Hodges et al 2020). Thus, the physically quantified differences in the coloration of house wren eggshells (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egg production provides a critical example of life-history theory in action as the investment into an egg and/or clutch will greatly influence the quality of that offspring, but, conversely, will reduce the parent's resources for both immediate self-maintenance and future reproductive investment [ 7 ]. This trade-off has been explored in the context of egg contents [ 8 ], such as androgen deposition in the yolk [ 9 , 10 ] and pigment deposition in the shell matrix [ 11 ], yet the production of the eggshell itself and its composition have not been considered within the same framework.…”
Section: Introductionmentioning
confidence: 99%
“…of egg contents [8], such as androgen deposition in the yolk [9,10] and pigment deposition in the shell matrix [11], yet the production of the eggshell itself and its composition have not been considered within the same framework.…”
Section: Introductionmentioning
confidence: 99%